Variable strut inclination model for shear design of FRP reinforced concrete members with shear reinforcement. (1st March 2020) - Kueres, Sophia; Hegger, Josef
Highlights: Development of a shear resistance model for members with FRP shear reinforcement. Determination of compression strut inclination depending on horizontal strain at middepth. Databank evaluation of proposed shear resistance model and comparison with existing code provisions. Derivation of an equation to determine the minimum shear reinforcement ratio of FRP reinforced concrete members. Abstract: To avoid brittle shear failures, the shear strength of reinforced concrete beams has to be verified at ultimate limit state. For this purpose, simple but accurate shear design provisions or shear resistance models are required. In this paper, the derivation of a simple shear design model for beams with FRP shear reinforcement is presented. At first, the suitability of existing code provisions and shear resistance models is evaluated using a large databank on shear tests on members with FRP shear reinforcement. Based on the results, a shear resistance model is developed based on a truss model with variable strut inclination, which is also the basis of the shear design of members with steel shear reinforcement according to current Eurocode 2. An important aspect regarding the derivation of the model is the definition of an appropriate method to determine the angle of the compression strut. For this purpose, a compression field model originally developed for steel reinforced concrete beams is adopted. The proposed resistance model is validated by means of a databank evaluation. Moreover, an equation to determine the minimum shear reinforcement ratio of FRP reinforced concrete members is derived based on the shear design provisions according to Eurocode 2.